Desain Animasi 2D Bertema Gizi "Gizi-Go: Pahlawan Cilik" untuk Anak Prasekolah - Aldi Fakhriansyah Subingat; Nugrahardi Ramadhani; Didit Prasetyo; Octaviyanti Dwi Wahyurini (Jurnal Ilmu Komputer dan Desain Komunikasi Visual, 2022)
In improving people's nutrition, it is possible to achieve quality human resources as early as possible, especially for preschool children (3-6 years old). In Indonesia, one of the nutritional problems, especially in pre-school-age children, is undernutrition and excess nutrition caused by consuming food that is not in accordance with the Guidelines for Balanced Nutrition and certain food preferences for children. Children's eating preferences have an important role so that children want to eat nutritious foods such as vegetables and fruit. Therefore, it is important to provide interesting nutrition education for children. Interesting media for preschool children is needed so that nutrition education for preschool children is conveyed. This design uses qualitative methods in the form of literature and existing studies. Furthermore, in making the animation, experimental studies were carried out, in-depth interviews with related experts, and conducting user tests on the target audience. The design produces a 2D animation entitled Gizi-Go: Little Heroes which tells the story of 4 children who have strength from the nutritious food they eat. Making animation is done with the Cut-Out technique so that the production process becomes more efficient.